The Clinton presidency and the constitutional system - Perotti, Rosanna (Joseph V. Hughes, Jr. and Holly O. Hughes series on the presidency and leadership., 2012)
Presidential scholars, former and current policymakers, and a former president bring varied insights and analyses to consider the impact, influence, and legacy of the presidency of William Jefferson Clinton, the "'New Democrat' from Hope, Arkansas."" In the eight years between 1993 and 2001, the Clinton White House presided over a booming economy that included a budget surplus in Clinton's second term, oversaw the most significant welfare reform since the New Deal, and wrestled with the challenge of developing a foreign-policy vision for the post-Cold War era